Anesthetic management in parturients with kyphoscoliosis - Thakur, Jay Prakash; Gurung, Tara; Shrestha, Sangeeta; Basnet, Ujjwal; Pradhan, AP (Nepal Journal of Obstetrics and Gynaecology, 2019)
Pregnancy in kyphoscoliotic woman is uncommon, with a reported incidence of 0.072%. It produces significant challenges for both anesthesiologist and obstetrician. Dealing with dual life, there is risk for both mother and fetus due to alterations in maternal physiology and change in spine anatomy. There are many case reports available with successful management both using spinal or general anesthesia. Here we present four case reports of successful management of such cases using general anesthesia or spinal anesthesia with palpatory and ultrasound guided method during a period of 6 months in Paropakar Maternity and Women’s Hospital.